175 A case series of anti-HMGCR immune mediated necrotizing myopathy: the West Midlands data. Issue 9 (12th August 2022) - San, Pyae Phyo; Davies, Nicholas; Srinivasan, Venkataramanan; Samra, Amrit; Paluri, Srinivasa; Ubben, Simon; Kumar, Prateek; Kiolachidis, Konstantinos; Dhar, Saikat; Moor, Carl-Christian
Abstract : Background: Among immune mediated myopathies, anti-3-hydroxy-3-methylglutaryl-coenzyme A reductase (anti-HMGCR) immune mediated necrotizing myopathy (IMNM) has been increasingly rec- ognised over the last two decades. Majority are associated with statin exposure and typically present with hovering high creatinine kinase (CK) and/or progressive proximal myopathy despite discontinuation of statin. Method: We analysed the data of 18 cases of anti-HMGCR IMNM from West Midlands region from 2016 to 2022. Results: 16 had statin exposure. Only 1 was asymptomatic but the rest experienced progressive proximal myopathy. Strikingly, two-thirds reported dysphagia and 3 required Intensive Unit admissions. Anti-HMGCR antibody was positive in all cases. CK levels remained high (mean=9053IU/l) despite dis- continuation of statin. A trend of persistently high ALT, lowering creatinine and weight loss reflected smouldering muscle loss. The asymptomatic patient did not need treatment. Significant improvement/remission was achieved spontaneously in 1, with steroids or IVIG alone in 10 and with combined immunotherapies in the rest. 1 patient died despite improvement in CK level. Conclusion: Anti-HMGCR IMNM, especially when associated with statin, responds well to immunotherapy. We suggest having a low threshold for checking anti-HMGCR antibody in patients with persistently high CK levels and/or proximal limb/pharyngeal muscle weakness, especially in the presence of statin exposure.